Development of an organizational and economic mechanism for the implementation of a product selection recommendation system - B.V. Kosogovskii (Цифровые модели и решения)
The study includes an analysis of existing problems that arise in the process of choosing a product, including complex technical devices. Based on the analysis, the paper proposes an organizational and economic mechanism that allows for the introduction of a recommendation system into the activities of an online store, which simplifies the process of choosing a product for the user. This tool will provide the organization with a competitive advantage and will increase website traffic, sales conversion and customer loyalty, which is especially relevant given the growing competition in online trading.